P.092 Successful implementation of a supported conversation program on an acute stroke unit. (November 2021) - Whelan, K; Haarstad, M; Feldbruegge, B; Jacobi, A; Mayo, C; Hautz, T; Heyer, C; Graham, B; Hunter, G
Abstract : Background: Aphasia is a life alerting deficit that affects up to 40% of people living with stroke. Barriers to communication ultimately impacts the care aphasic patients receive, as well as functional recovery. The Canadian Stroke Best Practice Recommendations suggest early and frequent language interventions to improve patients with aphasia quality of life, mood, and social outcomes. Methods: A supported conversation (SC) program (colloquially named The Aphasia Club) was implemented on the Acute Stroke Unit (ASU). The program included aphasia awareness and assessment training, as well as creation of an aphasia tool kit and discipline specific aphasia-friendly resources. Staff were encouraged to complete a 1-hour independent course on SC through the Aphasia Institute. Speech and language pathologists (SLP) offered an additional 30-minute in-person teaching session with interdisciplinary practice professionals. Following SLP assessment, personalized communication profiles were created for patients with aphasia to help staff understand the most useful strategies for communication. Results: More then 50 interprofessional staff members took SC training. Staff reported increased levels of knowledge and confidence when communicating with aphasic patients. Conclusions: A supported communication program was successfully implemented on an ASU. Planning appropriate communication interventions can assist interdisciplinary professionals in their ability to support patients through their stroke journey.